Traditional market, social relations, and diversity of edible plants traded in Beringharjo Market, Yogyakarta, Indonesia - Budiawati Supangkat ISKANDAR; Johan Iskandar; Dede Mulyanto; Rahman Latif Alfian; Suroso SUROSO (Society for Indonesian Biodiversity, 2021)
Abstract. Iskandar BS, Iskandar J, Mulyanto D, Alfian RL, Suroso. 2021. Traditional market, social relations, and diversity of edible plants traded in Beringharjo Market, Yogyakarta, Indonesia. Biodiversitas 22: 2012-2024. Although the modern markets have rapidly developed in many cities of Indonesia in the last decades, the urban traditional markets still exist in Indonesia, including Beringharjo Market, Yogyakarta. This study illustrated the story and social relation activities, biodiversity of edible plants traded, and market chain system of edible plant supplies from rural areas to Beringharjo Market. The study was conducted between February and March 2019. The method used in this study was qualitative data with an ethnobotanical approach. Some field techniques, including plant surveys and deep interviews with competent informants, were employed to collect the primary data. The result of this study showed that historically the economic activities of Beringharjo Market had been existing very a long time at least documented in 1758, while the market building was constructed by the Sultanate of Yogyakarta Palace, Sri Sultan Hamengku Buwono VIII in 1925. Like other traditional markets in Indonesia, the Beringharjo Market has played an important role in developing local economic activities, as the main place for the transaction of various edible plants and meeting for many ethnics, making the important as center of biocultural diversity at the local level. An ethnobotanical survey revealed that 93 edible plant species belonging to 37 families with a total of 159 landraces were commonly traded. The Beringharjo Market has traditionally traded a high diversity of edible plants that are supplied from local farmers productions of Yogyakarta and Central Java. Therefore, this traditional market has an important role in enhancing local economic development and contributing to promoting and conserving local plant diversity in this region.